KARAKTERISTIK PENGEMBANGAN KURIKULUM BAHASA ARAB MAHᾹRAH QIRᾹAH DAN KITᾹBAH - Wahdah, Yuniarti Amalia; Najihah, Nailin; Nasiruddin, Nasiruddin (STIQ Amuntai, 2023)
The purpose of this study is to describe the peculiarities of the growth of the Arabic learning curricula, particularly in the maharah qirāah and kitābah. The curriculum as a reference in learning has an important position. Consequently, it has always undergone development adapting to the development of human civilization. Curriculum development that occurs from time to time, requires educators to understand the characteristics of each curriculum. This study's research method makes use of library research. Data is gathered by locating and then examining a variety of literature, including books, journals, articles, and other materials that are relevant to the study's topic. The data is then subjected to content analysis. The study's findings indicate that Indonesia's Arabic learning curricula have undergone multiple iterations, each with unique qualities. The development of the Arabic curriculum in maharah qirāah and kitābah is adjusted to the level or level of learning which begins with determining learning objectives which will then determine the type of material, strategy and evaluation of learning in each maharah.